Development of method for identification the computer system state based on the decision tree with multidimensional nodes - Gavrylenko, Svitlana; Chelak, V. V.; Semenov, S. G. (Запорізький національний технічний університет, 2022)
Context. The problem of identifying the state of a computer system is considered. The object of the research is the process of computer system state identification. The subject of the research is the methods of constructing solutions for computer system state identification. Objective. The purpose of the work is to develop a method for decision trees learning for computer system state identification. Method. A new method for constructing a decision tree is proposed, combining the classical model for constructing a decision tree and the density-based spatial clustering method (DBSCAN). The simulation results showed that the proposed method makes it possible to reduce the number of branches in the decision tree, which will increase the efficiency of identifying the state of the computer system. Belonging to hyperspheres is used as a criterion for decision-making, which enables to increase the identification accuracy due to the nonlinearity of the partition plane and to perform a more optimal adjustment of the classifier. The method is especially effective in the presence of initial data with high correlation coefficients, since it combines them into one or more multivariate criteria. An assessment of the accuracy and efficiency of the developed method for identifying the state of a computer system is carried out. Results. The developed method is implemented in software and researched in solving the problem of identifying the state of the functioning of a computer system. Conclusions. The carried out experiments have confirmed the efficiency of the proposed method, which makes it possible to recommend it for practical use in order to improve the accuracy of identifying the state of a computer system. Prospects for further research may consist in the development of an ensemble of decision trees.

Актуальність. Розглянуто задачу ідентифікації стану комп’ютерної системи. Об’єктом дослідження є процес ідентифікації стану комп’ютерної системи. Предметом дослідження є методи побудови дерев рішень для ідентифікації стану КС Мета. Розробка методу побудови дерев рішень для ідентифікації стану комп’ютерної системи. Метод. Запропоновано новий метод побудови дерева рішень, який поєднує класичну модель побудови дерева рішень та оснований на щільності метод просторової кластеризації (DBSCAN). Результати моделювання показали, що запропонований метод надає можливість зменшити кількість розгалужень в дереві рішень, що дозволяє підвищити оперативність ідентифікації стану комп’ютерної системи. Використання приналежності до гіперсфер у якості критерію прийняття рішень, надає можливість підвищити точність ідентифікації за рахунок нелінійності площині розбиття та виконати більш оптимальне налаштування класифікатору. Метод є особливо ефективним за наявності вихідних даних, які мають високі кореляційні коефіцієнти, так як поєднує їх в один або декілька багатомірних критеріїв. Проведено оцінку точності та оперативності розробленого методу ідентифікації стану комп’ютерної системи. Результати. Розроблений метод реалізований програмно і досліджений під час розв’язання задачі ідентифікації стану функціонування комп’ютерної системи. Висновки. Проведені експерименти підтвердили працездатність запропонованого методу, що надає можливість рекомендувати його для практичного використання з метою підвищення точності ідентифікації стану комп’ютерної системи. Перспективи подальших досліджень можуть полягати в розробці ансамблю дерев рішень.
Розробка методу ідентифікації стану комп'ютерної системи на основі дерева рішень з багатовимірними вузлами
Keywords: computer system; abnormal state; identification; decision tree; clustering; DBSCAN algorithm; hypersphere; комп'ютерна система; аномальний стан; ідентифікація; дерево рішень; кластеризація; алгоритм DBSCAN; гіперсфера